Campuran Lateks Karet Alam-Stirena dan Poliisosianat sebagai Perekat Kayu Lamina Blends of Natural Rubber Latex-Styrene and Polyisocyanate for Laminated Wood Adhesive - Dede H Yulianto; Euis Hermiati (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
Each adhesive has its own strengths and weaknesses due to its bond strength, or its resistance to stress, heat, moisture and organisms.  Blending of several adhesives could combine properties of each.  Besides, it might reduce adhesives prices as well. In this research Natural Rubber Latex-Styrene (NRL-St) was blended with Polyisocyanate (PI) or API (Aqueous Polymer Isocyanate) adhesive. The aim of this research was to study the effects of compositions of adhesive blends on adhesive properties, and the effects of composition of adhesive blends and pressing time on bond strength of laminated wood (Acacia mangium). Blending compositions of NRL-St/PI were 100/0, 80/20, 60/40, 50/50, 40/60, 20/80, and 0/100. Physico-chemical properties of these blends of  adhesives, including solid content, pH, viscosity and mixtures homogenity were analyzed. Blends of NRL-St with PI adhesive had total solid contents range from 42.39 to 50.58%, pH from 7.45 to 7.98, and viscosity from 3506 to 5661 cp. Results of this study showed that optimum composition of blends of NRL-St and API adhesives for producing laminated wood of Acacia mangium was 50/50 (w/w).  At this composition the shear strength of laminated wood was 7.06 MPa, while delamination ratio in cold and boiling water were 0% and 4.89% respectively.  These values could meet Japan Agriculture Standard (JAS) for laminated wood (shear strength > 5.4 MPa and delamination ratio < 10%).  Optimum pressing time for producing laminated wood using API adhesive as well as blends of NRL-St/API (50/50) was two hours.